P38γ and p38δ reprogram liver metabolism by modulating neutrophil infiltration. (3rd February 2016) - González‐Terán, Bárbara; Matesanz, Nuria; Nikolic, Ivana; Verdugo, María Angeles; Sreeramkumar, Vinatha; Hernández‐Cosido, Lourdes; Mora, Alfonso; Crainiciuc, Georgiana; Sáiz, María Laura; Bernardo, Edgar; Leiva‐Vega, Luis; Rodríguez, Elena; et al.
Abstract: Non‐alcoholic fatty liver disease (NAFLD) is a major health problem and the main cause of liver disease in Western countries. Although NAFLD is strongly associated with obesity and insulin resistance, its pathogenesis remains poorly understood. The disease begins with an excessive accumulation of triglycerides in the liver, which stimulates an inflammatory response. Alternative p38 mitogen‐activated kinases (p38γ and p38δ) have been shown to contribute to inflammation in different diseases. Here we demonstrate that p38δ is elevated in livers of obese patients with NAFLD and that mice lacking p38γ/δ in myeloid cells are resistant to diet‐induced fatty liver, hepatic triglyceride accumulation and glucose intolerance. This protective effect is due to defective migration of p38γ/δ‐deficient neutrophils to the damaged liver. We further show that neutrophil infiltration in wild‐type mice contributes to steatosis development by means of inflammation and liver metabolic changes. Therefore, p38γ and p38δ in myeloid cells provide a potential target for NAFLD therapy. Synopsis: Mice lacking p38γ/δ in myeloid cells are protected against diet‐induced fatty liver. This effect is due to defective migration of p38γ/δ‐deficient neutrophils to the damaged liver, where they normally induce inflammation and metabolic changes. Expression of p38δ and p38γ is elevated in the liver from patients with non‐alcoholic fatty liver disease (NAFLD). p38γ/δ KO and myeloid‐specific p38γ/δ cKO mice are resistant to hepatic steatosis induced by high‐fat diet or methionine‐choline‐deficient diet. p38γ/δ control neutrophil migration to the damaged liver. Migration of neutrophils to the liver is necessary for the development of steatosis. Abstract : Mice lacking p38γ/δ in myeloid cells are protected against diet‐induced fatty liver. This effect is due to defective migration of p38γ/δ‐deficient neutrophils to the damaged liver, where they normally induce inflammation and metabolic changes.